Direct conversion of Teflon into nanodiamond films. Issue 11 (1st November 2020) - Gupta, Siddharth; Narayan, Jagdish
Abstract : We report a novel nonequilibrium approach for direct laser writing diamond by melting amorphous polytetrafluoroethylene (PTFE: (C2 F4 ) n ) in ambient conditions. The nanosecond laser pulses disintegrate PTFE, forming the undercooled molten carbon. This undercooled molten carbon regrows into diamond during the ultrafast melt quenching process, which lasts for ∼100 ns. HRTEM imaging, SAED, Raman, and EEL spectroscopy investigations confirm the first-order phase transformation of PTFE into single-crystalline <110> oriented diamond, which is associated with ultrafast unseeded crystallization. Our experimental findings open up a new pathway for the selective conversion of organic polymers into nano and microdiamonds and thin films with laser-writing. Impact statement: This research represents a fundamental breakthrough in selective conversion of PTFE polymeric films into single crystalline diamond thin films by pulsed laser annealing at near ambient conditions. GRAPHICAL ABSTRACT: UF0001